Atrial Fibrillation in Dengue Infection: A Self-limiting Phenomenon? (Two Case Reports) - Raymond Pranata; Wendy Wiharja; Vito Damay (ACI (Acta Cardiologia Indonesiana), 2018)
Dengue fever (DF) is highly prevalent in Indonesia as evidenced by 129,650 cases in 2015.Atrial fibrillation (AF) in dengue is exceptionally rare and usually self-limiting with resolution after recovery of illness. The aim of this case report is to depict two patients with AF in DF which resolves spontaneously in one and persists after infection in the other. Case 1 was 50 years old male presented with fever since 4 days before admission. NS1 antigen and IgM anti-Dengue virus were positive. An electrocardiogram (ECG) showed AF with rapid ventricular response (AFRVR). Case 2 was 53 years old male presented with dyspnea and palpitations 1 hour before admission. Patient had fever since 5 days before admission. Laboratory exams showed leukopenia, thrombocytopenia and positive IgM anti-Dengue virus. An electrocardiogram showed AFRVR. Intravenous fluids (normal saline), paracetamol, and digoxin were administered in both patients. They were admitted for close monitoring. Pre-discharge ECG of Case 1 showed resolution of AF. However, in Case 2, AF persists in pre-discharge ECG. In conclusion, physicians should be aware that a potentially reversible atrial fibrillation might be caused by this infection. It should be ensured that in those persisting cases, they should not be dismissed as just an ‘irreversible’ AF and progress into full-blown heart failure.